Translation Analysis in a Children's Storybook Entitled The Rainbow Fish - Mumtahanah, Qonita; Manggarrani, Maria Dita (Riwayat: Educational Journal of History and Humanities, 2025)
This study analyzes the translation shifts and translation methods applied in the children's storybook "The Rainbow Fish" by Marcus Pfister. Using a descriptive qualitative approach with a comparative methodology, this study examines the English source text and the Indonesian target text "The Rainbow Fish". Based on Catford's (1965) and Newmark's (2014) theories, 66 shifts were analyzed. The results show that structural shift dominates with 24 cases (36.4%), followed by class shift with 15 cases (22.7%), unit shift with 12 cases (18.2%), level shift with 8 cases (12.1%), and intra-system shift with 7 cases (10.6%). The translation is oriented to the target text by using a consistent communicative method, which proves effective in conveying moral messages to Indonesian children without losing the essence of the original story